Microbial characteristics analysis and kinetic studies on substrate composition to methane after microbial and nutritional regulation of fruit and vegetable wastes anaerobic digestion. (February 2018) - Zhao, Chunhui; Mu, Hui; Zhao, Yuxiao; Wang, Liguo; Zuo, Bin
Highlights: Enriched hydrogenotrophic methanogens in the inoculum accounted for the raised CH4 . The highest methane yield was 411 mL/g-VS with the substrate degradation of 91.2%. The optimal carbohydrate/protein/cellulose ratio for CH4 generation was 50:45:5. Modified Gompertz model can predict the biomethanation of carbohydrate-rich waste. Anaerobic granular sludge inoculum was fit for carbohydrate-rich waste digestion. Abstract: This study firstly evaluated the microbial role when choosing the acclimated anaerobic granular sludge (AGS) and waste activated sludge (WAS) as microbial and nutritional regulators to improve the biomethanation of fruit and vegetable wastes (FVW). Results showed that the enriched hydrogenotrophic methanogens, and Firmicutes and Spirochaeta in the AGS were responsible for the enhanced methane yield. A synthetic waste representing the mixture of WAS and FVW was then used to investigate the influences of different substrate composition on methane generations. The optimal mass ratio of carbohydrate/protein/cellulose was observed to be 50:45:5, and the corresponding methane yield was 411 mL/g-VSadded . Methane kinetic studies suggested that the modified Gompertz model fitted better with those substrates of carbohydrate- than protein-predominated. Parameter results indicated that the maximum methane yield and production rate were enhanced firstly and then reduced with the decreasing carbohydrate and increasing protein percentages; the lag phase time however increased continuously.